ANALISIS PENGARUH DISIPLIN KERJA, MOTIVASI KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN UNIVERSITAS SLAMET RIYADI SURAKARTA - Triyaningsih SL (INFORMATIKA, 2014)
Target of this research is; to test the significance of the influence of labor discipline, motivation, and organizational commitment partially and simultaneously on the performance of employees at the University of Slamet Riyadi Surakarta. This research type is quarantitative, that is in research which aim to abtain get satisfaction from a hypothesis by using predicted parametere test (test t) to test question instrument used by validity test and Reliability test. While classic assumption test which used by Multikoliniretas, Autocorelation, Heterokesdastisitas and Normalitas. Based on the results obtained by multiple linear regression equation: Y = -1,704 + 0,427X1 + 0,471X2 + 0,231X3. The results of the t test for variables work discipline obtained p-value 0.000